Intraspinal Pathology Associated With Pediatric Scoliosis: A Ten-year Review Analyzing the Effect of Neurosurgery on Scoliosis Curve Progression. Issue 20 (15th October 2016) - Jankowski, Pawel P.; Bastrom, Tracey; Ciacci, Joseph D.; Yaszay, Burt; Levy, Michael L.; Newton, Peter O.
Abstract : Study Design: This was a retrospective study of patients with Chiari I (CM I) and Chiari II (CM II) malformations, tethered cord syndrome, and syringomyelia examining the effect of neurosurgery on scoliosis. Objective: The aim of this study was to determine the factors affecting spinal deformity progression in patients with diseases of the neural axis following neurosurgical management. Summary of Background Data: There have been attempts to explain which factors influence the spinal deformity in diseases of the neural axis with varying results. Debate still exists as to the effectiveness of neurosurgery in curve stabilization. Methods: The medical records for patients treated over the past 10 years were reviewed. The spinal deformity surgical group consisted of patients who received surgery or progressed to surgical range (50°) and the nonsurgical group those who did not undergo fusion. Results: Fifteen patients (eight females and seven males) with scoliosis who underwent neurosurgical intervention were identified. Ten had tethered cord, six CM II, four CM I, and 11 syrinx. Average age at the time of neurosurgery was 7 ± 4 years (range 0.7–14 yrs). Following neurosurgery, no patients experienced improvement in their curves (defined as >10° decrease in Cobb angle), eight patients experienced stabilization (<10° decrease), and seven experienced worsening (>10° increase). The group that went on to spinal deformity surgery possessed larger curves before neurosurgery (mean 42°, range 20°–63°) than the nonsurgical group (19°, range 15°–26°; P  = 0.004). CM II patients had the greatest magnitude of curve progression, mean of 49°, compared with patients with CM I (6°) or tether cord without CM I or II (11°, P  = 0.01). Conclusion: Neurosurgical intervention may prevent curve progression in patients with scoliosis and Cobb angles < 30° if they do not have a complex CM II malformation. Patients with CM II are at a higher risk of curve progression and undergoing spinal fusion than patients with CM I, tethered cord syndrome, or syringomyelia. Level of Evidence: 4